VALIDASI METODE PENETAPAN KADAR HIDROKUINON PADA PRODUK KRIM PEMUTIH DENGAN METODE SPEKTROFOTOMETRI-UV - Wahyuningsih, Putri Dewi; Kusumowati, Ika Trisharyanti Dian (Jurnal Insan Farmasi Indonesia, 2024)
Whitening cream is a type of cosmetic product that contains organic chemicals or other substances that can lighten the skin. One of the additional chemicals found in whitening creams is hydroquinone. The mechanism of hydroquinone in lightening the skin involves inhibiting melanin production. According to BPOM Regulation No. 23 of 2019, hydroquinone is only allowed for use in artificial nail preparations at a maximum concentration of 0.02% after mixing before use. This study aims to identify the concentration of hydroquinone in whitening cream products available in the Madiun City area. Hydroquinone identification was conducted qualitatively using 5% FeCl3. The quantitative determination of hydroquinone concentration was performed using UV spectrophotometry. Based on the validation parameter calculations, the equation obtained is Y = 0.0463x - 0.0734, with linearity represented by a correlation coefficient (r) of 0.999, LOD of 0.549 ppm, and LOQ of 1.832 ppm, precision with %RSD of 0.9075%, and % recovery of 99.47%. From the test results, it was found that 4 out of 5 samples of whitening cream products contained hydroquinone, with sample B having a concentration of 1.31979%, sample C 1.05197%, sample D 0.89791%, and sample E 1.28956%.